Memorializing Tragedy on Twitter: Analyzing #PRAYFORORLANDO Following the 2016 Pulse Night Club Shooting. Issue 2 (4th March 2022) - Hardy, Molly M.; Miller, Brandon M.
ABSTRACT: The Pulse Nightclub Shooting in Orlando Florida became the deadliest mass shooting by a single shooter in the United States at the time and a profound attack on the marginalized community of LGBTQ. After a crisis social media can serve as a space for sharing emotions and making sense of tragedy. We conducted a thematic analysis to examine Twitter reaction to the Pulse Night Club shooting. In illuminating two themes of Unification and Division, we make connections between post-crisis social media narrative messaging and crisis narratives, as well as propose the addition of fractured narratives to the typology within contemporary digital culture.